1993
DOI: 10.1111/j.1432-1033.1993.tb17562.x
|View full text |Cite
|
Sign up to set email alerts
|

Lignin peroxidase L3 from Phlebia rediata

Abstract: The catalytic cycle of lignin peroxidase (Lip, ligninase) isozyme L3 from the white-rot fungus Phlebia radiata was investigated using stopped-flow techniques. Veratryl (3,4-dimethoxybenzyl) alcohol and a lignin model compound, non-phenolic a-0-4 dimer 1 -(3,4-dimethoxyphenyl)-2-(2-methoxyphenoxy)propane-1,3-diol, were used as electron donors. This is the first report on the detailed kinetic analysis of a Lip-catalysed Ca-CB bond cleavage of the dimer, representing the major depolymerisation reaction in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0
2

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 71 publications
4
42
0
2
Order By: Relevance
“…In contrast, Lundell et al (1993b) and Schoemaker et al (1994b) concluded a slightly different non-enzymatic reaction after Cα-Cβ cleavage assuming structure II (in Fig. 2) with a cation radical centre at the Cβ-ether oxygen position as consequence of LiP action.…”
Section: Roomentioning
confidence: 93%
See 1 more Smart Citation
“…In contrast, Lundell et al (1993b) and Schoemaker et al (1994b) concluded a slightly different non-enzymatic reaction after Cα-Cβ cleavage assuming structure II (in Fig. 2) with a cation radical centre at the Cβ-ether oxygen position as consequence of LiP action.…”
Section: Roomentioning
confidence: 93%
“…Here, the catalytic cycle will be initiated again by H 2 O 2 to form E I . E I further reacts with adlerol (structure I) to E II and an adlerol cation radical intermediate (structure II) (Lundell et al, 1993b) which will be rapidly fragmented non-enzymatically between its Cα-Cβ bonds in the subsequent (Hatakka et al, 1991). For the latter, various theories have been under consideration.…”
Section: Roomentioning
confidence: 99%
“…Furthermore, the main J? radiata LIP isozyme L3 is kinetically similar to p chrysosporium LIP H8 [9]. The characterized R radiata MnP also resembles biochemically the E!…”
Section: Introductionmentioning
confidence: 66%
“…Extracellular proteins were separated by FPLC anion-exchange chromatography at pH 5.5 on Sepharose Q (Pharmacia Biotechnology) as described previously [2,9]. Enzyme activities of protein fractions were analyzed and the peak fractions showing only laccase, MnP or LiP activity were pooled and concentrated (10 kDa cut-off Microsep concentrators, Filtron).…”
Section: Purification Of Enzymesmentioning
confidence: 99%
“…These enzymes are relatively nonspecific, and can therefore oxidize phenolic aromatic substrates as well as various non-phenolic lignin model compounds [59][60][61]. The importance of lignin peroxidases for lignin depolymerization reflects their ability to catalyze the cleavage of α,β and β-ether bonds (including β-O-4 linkages) leading to the efficient degradation of lignin into mono-aromatic structures, which has been demonstrated using lignin model compounds [61].…”
Section: Enzymes Involved In Fungal Lignin Degradationmentioning
confidence: 99%